Intimate Commerce : Exchange, Gender, and Subjectivity in Greek Tragedy - Wohl, Victoria, 1966- (Book collections on Project MUSE., 1998)
Analyzes how the exchange of women between men in Greek tragedies was portrayed as disastrous for both the men and women involved and argues that the use of women as objects of commerce affirmed the reigning ideologies of the era. -- Provided by publisher.